Pediatric patients with RASopathy-associated hypertrophic cardiomyopathy: the multifaceted consequences of PTPN11 mutations - Giulio Calcagni (Orphanet Journal of Rare Diseases, 2019)
Abstract The concomitant occurrence of hypertrophic cardiomyopathy and congenital heart defect in patients with RASopathies has previously been reported as associated to a worse clinical outcome, particularly closed to cardiac surgery. Different mechanisms of disease have been demonstrated to be associated with the two classes of PTPN11 mutations underlying Noonan syndrome and Noonan syndrome with multiple lentigines (also known as LEOPARD syndrome). Although differential diagnosis between these two syndromes could be difficult, particularly in the first age of life, we underline the relevance in discriminating these two disorders in terms of affected signaling pathway to allow an effective targeted pharmacological treatment.